External Variables in the Expansion of Employment Opportunities - Hadiyanti, Sofia Ulfa Eka (Universitas Muhammdaiyah Surakarta, 2013)
This study aimed to investigate the effect of external variables on employment in the province of East Kalimantan. Besides, it will also discuss how the direct and indirect influence some of these external variables on employment in the province of East Kalimantan. External variables studied were foreign investment, domestic investment, government expenditure, and Gross Regional Product (GRP) in East Kalimantan Province. This study uses time series data from 2002 to 2011. To determine the effect of the direct and indirect pathway analysis is used (pathanalysis). If you see from pathway analysis obtained is known that foreign investment and government expenditure directly affect positively. Domestic investment negatively affect GRP in East Kalimantan. Direct influence of foreign investment and government expenditure on employment is negative. Effect of indirect foreign investment and government expenditure on employment by GRP in East Kalimantan Province is negative. While domestic investment indirect effect on employment through the GRP is positive. While domestic investment and GRP direct positive effect on employment in the province of East Kalimantan.